Fenomena Test Drive sebelum Menikah : Perspekftif Islam dan Dampaknya - Pratama, Andy Riski; Rawati, Mesis; Effendy, Yolanda (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The phenomenon of test drives before marriage, which involves sexual intercourse or cohabitation before legal marriage, is increasingly common in modern society. This article explores the phenomenon from an Islamic perspective and analyzes its social, psychological and spiritual impacts. The research used a descriptive approach with qualitative methods to explore Islamic views on test drive relationships before marriage and their impact on individuals and society. Data was obtained from journals, books, and websites as sources. In Islam, sexual intercourse before marriage is considered zina, which contradicts religious teachings that emphasize chastity and honor. The impacts include moral decline, divorce and emotional instability. This research highlights the importance of maintaining religious and moral values in the face of this phenomenon as well as the need for collective efforts from various parties to overcome its negative impacts. Thus, this article proposes solutions through proper religious understanding, social media monitoring by parents, quality sexual education in schools, and government regulation of unsavory content on casual sex.